Stages and analysis of language integrated skills. Mades of integrating all four skills - Yo`ldosheva Mohlaroy; Mirzayeva Mahbuba Mamajonovna (Journal of Innovation in Education and Social Research, 2023)
Integrating all four language skills (listening, speaking, reading, and writing) is crucial for a comprehensive language learning experience. It allows learners to develop a well-rounded proficiency in the language. Here are the stages and analysis of language integrated skills